2017
DOI: 10.1002/jsfa.8733
|View full text |Cite
|
Sign up to set email alerts
|

Natural vitamin B12 and fucose supplementation of green smoothies with edible algae and related quality changes during their shelf life

Abstract: 20BACKGROUND: Some algae are an excellent source of vitamin B12, of special

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 51 publications
(115 reference statements)
0
18
0
Order By: Relevance
“…presents 1 g/kg fresh weight of vitamin B 12 . Castillejo et al [169] tested seven seaweed and two microalgae, despite the low levels of vitamin B 12 in Porphyra when compared to microalgae. This quantity would be enough to suppress the vitamin B 12 daily need of a person when added to a smoothie.…”
Section: Vitaminsmentioning
confidence: 99%
See 1 more Smart Citation
“…presents 1 g/kg fresh weight of vitamin B 12 . Castillejo et al [169] tested seven seaweed and two microalgae, despite the low levels of vitamin B 12 in Porphyra when compared to microalgae. This quantity would be enough to suppress the vitamin B 12 daily need of a person when added to a smoothie.…”
Section: Vitaminsmentioning
confidence: 99%
“…For example, air-dried Pyropia tenera has produced biologically inactive B 12 . In opposition, the lyophilization process might have improved nutritional quality due to the presence of active vitamin B 12 [169].…”
Section: Vitaminsmentioning
confidence: 99%
“…Microalgae-containing plant-based soups and beverages have been also formulated. For example, Castillejo et al [42] studied the quality changes of smoothies prepared containing several algae including macroalgae and the microalgae Chlorella vulgaris and Spirulina spp. (at a concentration of 2.2%) as well as grapes, broccoli, and cucumber.…”
Section: Beverages and Dairy Productsmentioning
confidence: 99%
“…Certain SW extracts have been used worldwide as biofertilizers and biostimulants as they are biodegradable, non‐toxic, non‐polluting and non‐hazardous to humans, animals and the environment . SW extracts are classified as biostimulants because they contain bioactive substances (macro‐ and micronutrients, amino acids, vitamins, alginic acid, mannitol, phytohormones, antioxidants) that at low concentrations can exhibit growth‐stimulating properties . Commercial SW products can be used as liquid extracts applied as foliar spray and soil drench, or in granular/powder form as soil amendments …”
Section: Introductionmentioning
confidence: 99%
“…1 SW extracts are classified as biostimulants because they contain bioactive substances (macro-and micronutrients, amino acids, vitamins, alginic acid, mannitol, phytohormones, antioxidants) that at low concentrations can exhibit growth-stimulating properties. 5 Commercial SW products can be used as liquid extracts applied as foliar spray and soil drench, or in granular/powder form as soil amendments. 6,7 Many researchers have reported that SW extracts promoted growth and increased yield and quality of vegetables crops such as cucumber (Cucumis sativus L.), 8 tomato (Solanum lycopersicum L.), 2,9 broccoli (Brassica oleracea var.…”
Section: Introductionmentioning
confidence: 99%